2010
DOI: 10.1371/journal.pntd.0000887
|View full text |Cite
|
Sign up to set email alerts
|

Complex Interactions between Soil-Transmitted Helminths and Malaria in Pregnant Women on the Thai-Burmese Border

Abstract: BackgroundDeworming is recommended by the WHO in girls and pregnant and lactating women to reduce anaemia in areas where hookworm and anaemia are common. There is conflicting evidence on the harm and the benefits of intestinal geohelminth infections on the incidence and severity of malaria, and consequently on the risks and benefits of deworming in malaria affected populations. We examined the association between geohelminths and malaria in pregnancy on the Thai-Burmese border.MethodologyRoutine antenatal care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
77
5
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 68 publications
(75 reference statements)
8
77
5
1
Order By: Relevance
“…[4][5][6]17 In this study, we focused on the interaction between schistosomiasis and malaria infection. Several biological studies have shown a synergistic effect of coinfection, 16,[18][19][20][21] whereas other studies suggested an acceleration or regulation toward protective profile of the acquired immunity against malaria in children coinfected with malaria and schistosomiasis 9,22 and another study did not find an association. 23 A study on children conducted in Mali in 2002-2003 presented both epidemiological and biological approaches and concluded on a protective effect of infection with urinary schistosomiasis on malaria.…”
Section: Discussionmentioning
confidence: 93%
“…[4][5][6]17 In this study, we focused on the interaction between schistosomiasis and malaria infection. Several biological studies have shown a synergistic effect of coinfection, 16,[18][19][20][21] whereas other studies suggested an acceleration or regulation toward protective profile of the acquired immunity against malaria in children coinfected with malaria and schistosomiasis 9,22 and another study did not find an association. 23 A study on children conducted in Mali in 2002-2003 presented both epidemiological and biological approaches and concluded on a protective effect of infection with urinary schistosomiasis on malaria.…”
Section: Discussionmentioning
confidence: 93%
“…Although we did not collect data on parasite infection, we can infer that drinking unboiled water, especially from a spring or river, easily caused parasite infections, which led to intestinal bleeding and anemia. 25,26 Boel and others 27 reported that the prevalence of helminth infection in Karen and Burmese pregnant women on the Thai-Burmese border was as high as 70%.…”
Section: Discussionmentioning
confidence: 99%
“…According to the recent report, the prevalence of helminths infection was as high as 70% in Burmese pregnant women on the Thailand/Burma border. 23 Drinking unboiled water is related to parasitic infection. 20 In the investigation, another limitation is that we used only a brief food frequency to estimate the status of food intake; as a result, the status of micronutrient intake or total caloric intake of the subjects was not accessed.…”
Section: Discussionmentioning
confidence: 99%